Human Rights and Oppressed Peoples : Collected Essays and Speeches - Brandes, Georg, 1842-1927 (The University of Wisconsin Press, 2020)
"Georg Brandes was called the 'Father of the Modern Breakthrough, ' a nickname he gained from his lectures critical of the romanticism movement in literature. A prominent writer, thinker, and speaker at the turn of the twentieth century, his works often considered intellectual topics beyond the literary criticism he was best known for. In this collection, William Banks has translated a number of Brandes's essays and speeches that engage in the concerns of oppressed peoples. By putting these works into context, Banks reintroduces Brandes as a major progenitor of the human rights movement"--